An investigation of high speed metal forming with liquid shock waves. - Kosing, Oliver E (My University, 1998)
In this work a new high speed metal forming process is experimentally and theoretically investigated and discussed. The high speed metal forming is carried out in a liquid shock tube. The pressure energy of a liquid shock wave, which is generated non-explosively is used to form the metal workpiece.(abbreviation abstract)
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johanneaburg, in fulfilment of the requirerments for the degree of Doctor of Philosophy.
Keywords: Shock waves.; Shock tubes.